2012
DOI: 10.1103/physrevlett.109.055001
|View full text |Cite
|
Sign up to set email alerts
|

Lower Hybrid Drift Waves: Space Observations

Abstract: Lower hybrid drift waves (LHDWs) are commonly observed at plasma boundaries in space and laboratory, often having the strongest measured electric fields within these regions. We use data from two of the Cluster satellites (C3 and C4) located in Earth's magnetotail and separated by a distance of the order of the electron gyroscale. These conditions allow us, for the first time, to make cross-spacecraft correlations of the LHDWs and to determine the phase velocity and wavelength of the LHDWs. Our results are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
146
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(167 citation statements)
references
References 17 publications
21
146
0
Order By: Relevance
“…[1][2][3] Indeed, electromagnetic fluctuations in the lower-hybrid frequency range are frequently observed in the vicinity of reconnection sites in both space (e.g., Refs. [4][5][6][7][8][9] and laboratory plasmas (e.g., Refs. [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Indeed, electromagnetic fluctuations in the lower-hybrid frequency range are frequently observed in the vicinity of reconnection sites in both space (e.g., Refs. [4][5][6][7][8][9] and laboratory plasmas (e.g., Refs. [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7f presents the fluctuations of the electric field in the wave propagation direction (δE k ) and parallel magnetic field (δB || ) with a bandpass filtering for frequencies 10 Hz < f < 300 Hz. Then the wave potential is estimated by B = (B 0 /n e eµ 0 )δB || (Norgren et al, 2012;Divin et al, 2015), which peaks at ∼ 20 eV as shown in Fig. 7g.…”
Section: Observationmentioning
confidence: 99%
“…When C3 and C4 were at 40 km from each other in the magnetotail in August 2007 (number 11 in Fig. 2), lower hybrid drift waves, a special type of plasma wave that develops in thin boundaries both in space and in the laboratory, were detected and characterised by Norgren et al (2012). These waves were detected at a sharp gradient in density and magnetic field.…”
Section: Plasma Sheet Dynamicsmentioning
confidence: 93%